The Calcium Carbonate Shell of Emiliania huxleyi Provides Limited Protection Against Viral Infection - Haunost, Mathias; Riebesell, Ulf; Bach, Lennart T. (Frontiers in Marine Science, 2020)
Coccolithophores are a group of marine phytoplankton which cover themselves with the coccosphere - a shell composed of numerous calcium carbonate (CaCO3) platelets. They play a pivotal role in the oceanic carbon and calcium carbonate cycles, as they contribute significantly to the marine primary production and account for a large proportion of the pelagic CaCO3 production. Despite more than a century of coccolithophore research, it remains speculative why coccolithophores calcify. However, resolving this question is essential to assess the competitive fitness of this important group in the future ocean where changes in calcification are expected. Here, we used the Emiliania huxleyi – Emiliania huxleyi virus 86 host-virus model system to test the hypothesis that the coccosphere serves as a physical barrier reducing viral infection. Therefore, we removed the coccosphere from living E. huxleyi cells and compared the infection progress relative to calcified cells in a series of 6 experiments under different growth conditions. These experiments showed that the CaCO3 shell provides limited protection directly after cell division when the coccosphere has been shared among the two daughter cells and is therefore permeable for viral particles. However, the coccosphere can reduce viral infection and the protection improves as the number of calcite platelets in the coccosphere increases. Our results indicate that E. huxleyi can reach higher abundances in blooms that are infested with large viruses due to the protective role of the coccosphere. The findings improve our understanding of the ecological role of calcification.